Chapter 8 Medical Discourse and Ideology in the Edinburgh Review: A Chaldean Exemplar Scottish Journalism in the Age of Enlightenment - Brown, Rhona (The Enlightenment World, 2015)
Scotland was at the forefront in spreading the ideas of the Enlightenment. By the beginning of the nineteenth century its periodical press enjoyed an unparalleled reputation with magazines like Blackwood's Magazine and the Edinburgh Review enjoying wide circulation. This collection of essays is the result of a major conference focusing specifically on the role of Scotland's print culture in shaping the literature and politics of the long eighteenth century. In contrast to previous studies, this work treats Blackwood's as the culmination of a long tradition rather than a starting point. It will appeal to scholars of the European Enlightenment as well as those researching Scottish literature and politics, and Romanticism.